In-depth Analysis of The Learning Process in Schools: Reviewing The Quality of Students' Actual Mastery of Concepts on Temperature and Heat Material - Sofna, Ayu; Zakwandi, Rizki; Purwasih, Desy (International Journal of Education and Teaching Zone, 2024)
This research aims to determine students' mastery of concepts regarding temperature and heat in the learning process. Researchers used a quantitative approach with a Quasi-Experimental method in this research. This research was conducted at SMK Negeri 09 Muaro Jambi. The population in this study was all class X at SMK Negeri 09 Muaro Jambi. Sampling used a purposive sampling technique with consideration of teachers who taught in the same class, namely class X TBSM 1 and X TBSM 2, totalling 24 and 26 students. Data was obtained by giving a concept mastery test in 5 essay questions. After being given the test, the data was analyzed, and the results showed that students' mastery of concepts in temperature and heat material was in a low category. This is proven in question number 1, where as many as 60% of students answered with a value of 0; in question number 2, as many as 80% of students responded with a value of 1; in question number 3, as many as 72% of students answered with a value of 1, question number 4 as many as 62% of students answered with a value one, and for question number 5, 52% of students responded with a score of 0. Indikator that more than 50% of students' concept mastery abilities could be higher.